Urogenital immune signatures are associated with birth outcomes after maternal urinary tract infection - Samantha Ottinger; Addison B. Larson; Vicki Mercado-Evans; Holly Branthoover; Jacob J. Zulk; Camille Serchejian; Libbie Ogilvie; Marlyd E. Mejia; Zainab A. Hameed; Ryan Walde; Rachel C. Fleck; Christopher S. Ward; et al. (Science Translational Medicine, 2026)
Preterm birth is the leading cause of infant mortality, resulting in more than 1 million neonatal deaths globally each year. Maternal urinary tract infection (UTI) during pregnancy increases risk for preterm birth; however, biological processes mediating UTI-associated preterm birth are not well described. We established a murine maternal UTI model in which challenge with uropathogenic Escherichia coli (UPEC) initiated preterm labor and birth in about half of dams. Although bacterial burdens were similar, dams experiencing preterm birth displayed excessive bladder inflammation, elevated placental and decidual cytokines, higher proportions of male fetuses, and lower maternal serum interleukin-10 (IL-10) compared with nonlaboring dams. Exogenous IL-10 or lymph node sequestration of T cells reduced placental type 17 T helper cells (T H 17 cells) and abrogated preterm birth. In a human pregnancy cohort, we correlated urinary cytokines with birth outcomes and urine culture status. These analyses yielded an exploratory, noninvasive culture-agnostic system for evaluating preterm birth risk, implicating T cell–related cytokines including IL-10, IL-15, GM-CSF, and RANTES. These findings demonstrate that our murine model provides a platform to investigate immunological and microbial factors governing UTI-associated preterm birth and, coupled with patient samples, may be used to identify candidate biomarkers and mechanistic targets for future investigation.